2021
DOI: 10.1080/22221751.2021.1878937
|View full text |Cite
|
Sign up to set email alerts
|

Saliva viral load better correlates with clinical and immunological profiles in children with coronavirus disease 2019

Abstract: Background Pediatric COVID-19 studies exploring the relationships between NPS and saliva viral loads, clinical and immunological profiles are lacking. Methods Demographics, immunological profiles, nasopharyngeal swab (NPS), and saliva samples collected on admission, and hospital length of stay (LOS) were assessed in children below 18 years with COVID-19. Findings 91 patients were included between March and August 20 20. NPS and saliva viral l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…Notably, compared to age-matched males, young females (<38 years old) showed lower salivary viral load that increases with age, while no clear age-related effects were found in males. Clinical severity and immunological profiles seem to better correlate with viral load in saliva than in NOP swabs [38,39], so our findings could be attributed to distinct immune responses between genders leading to higher viral shedding and disease severity in males [40], and could also explain the higher proportion of asymptomatic females in couples positive for SARS-CoV-2 [41]. These observations further suggest that salivary viral load together with older age, male gender and other risk factors could be important to predict disease duration, severity and mortality [39,42].…”
Section: Discussionmentioning
confidence: 95%
“…Notably, compared to age-matched males, young females (<38 years old) showed lower salivary viral load that increases with age, while no clear age-related effects were found in males. Clinical severity and immunological profiles seem to better correlate with viral load in saliva than in NOP swabs [38,39], so our findings could be attributed to distinct immune responses between genders leading to higher viral shedding and disease severity in males [40], and could also explain the higher proportion of asymptomatic females in couples positive for SARS-CoV-2 [41]. These observations further suggest that salivary viral load together with older age, male gender and other risk factors could be important to predict disease duration, severity and mortality [39,42].…”
Section: Discussionmentioning
confidence: 95%
“…However, there are a few studies of paediatric patients and different ways to sampling for SARS-CoV-2 detection and their results are conflicting [5][6][7] . Our results showed that saliva had the same diagnostic performance than that of NPS for SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, compared to age-matched males, young females (< 38 years old) showed lower salivary viral load that increases with age, while no clear age-related effects were found in males. Clinical severity and immunological profiles seem to better correlate with viral load in saliva than in NOP swabs (35,36), so our findings could be attributed to distinct immune responses between genders leading to higher viral shedding and disease severity in males (37), and could also explain the higher proportion of asymptomatic females in couples positive for SARS-CoV-2 (38). These observations further suggest that salivary viral load together with older age, male gender and other risk factors could be important to predict disease duration, severity and mortality (36,39).…”
Section: Discussionmentioning
confidence: 82%